In Utero Cocaine Exposure and Infant Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The effects on neurobehavior in 20 infants with prenatal exposure to cocaine, alcohol, marijuana, and cigarettes, compared to 17 infants exposed to alcohol and/or marijuana and cigarettes without cocaine and 20 drug-free infants, were assessed using the Neonatal Intensive Care Unit Network Neurobehavioral Scale at Brown University School of Medicine, Women and Infants Hospital, Providence, RI.